Effect Of Industry And Service Sectors On Goods And Services Tax Revenue In The G20: Per Capita Income As A Moderator - Dhinnessa Prabowo; Suparna Wijaya (WIM Solusi Prima, 2023)
This research aims to examine the factors influencing the tax revenue from goods and services in G20 countries. After conducting various tests and analyses, it was found that the best model for this study is the Fixed Effect (FE) model. The analysis revealed that both the contribution of the industrial sector to GDP and the contribution of the service sector to GDP have a significant positive effect on tax revenue from goods and services. Additionally, per capita income also positively and significantly influences tax revenue. However, when moderated by per capita income, the positive effect of the industrial and service sectors on tax revenue weakened. This suggests that countries heavily reliant on a specific industrial sector for their GDP and tax revenue may face higher risks if that sector fluctuates. Similarly, if a country's economy is dominated by other sectors, the positive influence of the service sector on tax revenue might be hindered. Based on the results of this research, recommendations can be made for governments to enhance support for both the industrial and service sectors, diversify the economic structure to reduce dependency risks on a single sector, and formulate policies that foster inclusive economic growth and increased per capita income. Taking proactive measures based on the findings of this research is expected to enable G20 countries to achieve strong, sustainable, and inclusive economic growth, aligning with the objectives of the G20 formation.